Stable isotope insights into the weathering processes of a phosphogypsum disposal area. (1st September 2018) - Papaslioti, Evgenia-Maria; Pérez-López, Rafael; Parviainen, Annika; Macías, Francisco; Delgado-Huertas, Antonio; Garrido, Carlos J.; Marchesi, Claudio; Nieto, José M.
Abstract: Highly acidic phosphogypsum wastes with elevated potential for contaminant leaching are stack-piled near coastal areas worldwide, threatening the adjacent environment. Huge phosphogypsum stacks were disposed directly on the marshes of the Estuary of Huelva (SW Spain) without any impermeable barrier to prevent leaching and thus, contributing to the total contamination of the estuarine environment. According to the previous weathering model, the process water ponded on the surface of the stack, initially used to carry the waste, was thought to be the main washing agent through its infiltration and subsequently the main component of the leachates emerging as the edge outflows. Preliminary restorations have been applied to the site and similar ones are planned for the future considering process water as the only pollution agent. Further investigation to validate the pollution pathway was necessary, thus an evaluation of the relationship between leachates and weathering agents of the stack was carried out using stable isotopes (δ 18 O, δ 2 H, and δ 34 S) as geochemical tracers. Quantification of the contribution of all possible end-members to the phosphogypsum leachates was also conducted using ternary mixing via the stable isotopic tracers. The results ruled out ponded process water as main vector of edge outflow pollution and unveiled a continuous infiltration of estuarine waters to the stack implying that is subjected to an open weathering system. The isotopic tracers revealed a progressive contribution downstream from fluvial to marine signatures in the composition of the edge outflows, depending on the location of each disposal zone within the different estuarine morphodynamic domains. Thus, the current study suggests that the access of intertidal water inside the phosphogypsum stack, for instance through secondary tidal channels, is the main responsible for the weathering of the waste in depth, underlying the necessity for new, more effective restorations plans. Graphical abstract: Image 1 Highlights: Leachates from a phosphogypsum stack adversely affect estuarine environments. Stable isotopes were used as environmental tracers to track origin of the leachates. Infiltration of surface process water was ruled out as the main vector of pollution. The stack is an open system with estuarine water input as the main weathering agent. Unravelling weathering process is essential to plan effective restoration actions.